Quest for knowledge in a world of politics: - Sandra Rebok (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien)
Alexander von Humboldt not only managed to navigate his scientific exploration voyages through different political contexts, also Humboldtian Science as such clearly contains political facets. In the regions he visited, his eyes were not merely set on a description of the natural world; his interests always included the socio-political conditions under which its inhabitants lived. What the cosmopolitan explorer envisioned was much more than an enterprise confined to advancing the borders of knowledge; his project also had social connotations in the broadest sense. Combining different areas of knowledge allowed him to obtain new insights, and with this acumen, he aimed to influence the course of societal development. In this sense, Humboldtian Science pursued an aim that can be seen as political: creating and using knowledge for human progress and pointing to social injustice, abuses, and corruption.